2010
DOI: 10.4049/jimmunol.0903147
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Feature of Toll/IL-1 Receptor Domain-Containing Adaptor Protein Is Partially Responsible for Lipopolysaccharide Insensitivity in Zebrafish with a Highly Conserved Function of Myd88

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…In fact, there have been other reports that illustrate similar findings, that indeed MyD88 is present in aggregate structures in the cytoplasm (23,25). Furthermore, this seems to be a characteristic of MyD88 that is conserved across species (29). A recent study by Liu et al show that zebrafish MyD88 is also expressed as large condensed spots in the cytoplasm of cells, and this observation is reproducible in different cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…In fact, there have been other reports that illustrate similar findings, that indeed MyD88 is present in aggregate structures in the cytoplasm (23,25). Furthermore, this seems to be a characteristic of MyD88 that is conserved across species (29). A recent study by Liu et al show that zebrafish MyD88 is also expressed as large condensed spots in the cytoplasm of cells, and this observation is reproducible in different cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…Rebl et al, 2009). Recently, Liu et al (2010) detected experimentally that TLRs need to use MyD88 directly to convert signalling to NF-B and IFN-␤ in zebrafish, thus confirmed the downstream of MyD88-dependent TLR signal pathway was conserved in zebrafish and mammals. Earlier investigation showed that MyD88-knock-out embryos of zebrafish harboured 100-1000-fold more bacteria than the wild type MyD88 embryos when injected with the pathogenic bacterium Salmonella enterica, revealing the role of MyD88 in fish immune response (van der Sar et al, 2006).…”
Section: Discussionmentioning
confidence: 80%
“…It was also shown that in Japanese flounder the number of MyD88-expressing cells increased in spleen and kidney after the infection of Edwardsiella tarda, and the MyD88 expression was further up-regulated in peripheral blood leucocytes when stimulated with LPS, Poly(I:C) and peptidoglycan (Takano et al, 2006). Although the bacterial number was not quantified in the V. alginolyticus-infected fish, the increased expression of TLR1 and TLR2, as well as MyD88 genes in spleen and kidney of the orange-spotted groupers injected with V. alginolyticus and with LPS and Poly(I:C) may in fact imply, as shown in Japanese flounder and in zebrafish (Takano et al, 2006;Liu et al, 2010), the activation of MyD88-dependent pathway in the grouper, leading to the induction of IL-1␤. Recent study also reported the increased expression of IL-1␤ via TLR2 in carp macrophages when stimulated with peptidoglycan (Ribeiro et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Some of these components are known to trigger the activation of Toll-like receptors (TLRs) or activate intracellular signalling molecules, including the nucleotide-binding-domain-and leucine-rich-repeat-containing family proteins (NLRs). The importance of these pathways is being defined in the zebrafish, and their contribution to host defence against infectious agents in vertebrates is being dissected in detail (Meijer et al, 2004; van der Sar et al, 2006; Hall et al, 2009; Sepulcre et al, 2009; Stockhammer et al, 2009; Sullivan et al, 2009; Liu et al, 2010; Palti, 2011). Zebrafish genetic knockouts of components of these pathways are eagerly awaited.…”
Section: Granulocytes: the First Wavementioning
confidence: 99%